2019
DOI: 10.20937/rica.2019.35.01.07
|View full text |Cite
|
Sign up to set email alerts
|

Evaluación Del Riesgo Ambiental De Metales Pesados en Los Sedimentos Superficiales Del Saco Del Golfo De Cariaco

Abstract: Palabras clave: factor de enriquecimiento, índice de geoacumulación, probabilidad tóxica RESUMEN El objetivo de esta investigación fue evaluar la potencialidad de algunos metales pesados para provocar daños al ecosistema del golfo de Cariaco. Para ello se determinaron las concentraciones de los metales en los sedimentos y los índices de contaminación y riesgo ambiental. Además, se realizó una prueba de supervivencia con Artemia salina. Las concentraciones totales (µg/g) fueron: Cu (29-91, Χ-= 58), Cd (1.9-4.9,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 26 publications
2
3
0
5
Order By: Relevance
“…When the EF values of surface sediments of Lake Maracaibo are compared with those of other aquatic ecosystems (Table S1), it is observed that the As and Pb levels are higher than those of the Bay of Bengal, Bangladesh [63], which has been described as an environment with a high level of anthropogenic impact. Regarding the EF-Cd values, these are similar to those of the Gulf of Cariaco, Venezuela [62], whose pollution degree is moderately severe. Likewise, the enrichment values for Ni and Cu are lower than those of Chaohu Lake, China [14] and Gulf of Cariaco, Venezuela [62], with moderate anthropic impact levels.…”
Section: Elemental Enrichment Levels In Surface Sedimentssupporting
confidence: 64%
See 3 more Smart Citations
“…When the EF values of surface sediments of Lake Maracaibo are compared with those of other aquatic ecosystems (Table S1), it is observed that the As and Pb levels are higher than those of the Bay of Bengal, Bangladesh [63], which has been described as an environment with a high level of anthropogenic impact. Regarding the EF-Cd values, these are similar to those of the Gulf of Cariaco, Venezuela [62], whose pollution degree is moderately severe. Likewise, the enrichment values for Ni and Cu are lower than those of Chaohu Lake, China [14] and Gulf of Cariaco, Venezuela [62], with moderate anthropic impact levels.…”
Section: Elemental Enrichment Levels In Surface Sedimentssupporting
confidence: 64%
“…Regarding the EF-Cd values, these are similar to those of the Gulf of Cariaco, Venezuela [62], whose pollution degree is moderately severe. Likewise, the enrichment values for Ni and Cu are lower than those of Chaohu Lake, China [14] and Gulf of Cariaco, Venezuela [62], with moderate anthropic impact levels.…”
Section: Elemental Enrichment Levels In Surface Sedimentssupporting
confidence: 64%
See 2 more Smart Citations
“…Como toda zona resguardada, la energía del agua es baja y las partículas se transportan preeminentemente suspendidas, lo cual justifica la presencia de sedimentos mal clasificados con detritos de rocas sedimentarias, esqueletos, conchas de moluscos, arrecifes (Fuentes-Hernández et al 2019) La fracción gruesa del sedimento seco (> 2 mm) fue separada por tamización en un equipo Ro-Tap con una columna Tyler; mientras que las fracciones menores, limo y arcilla, por sedimentación, con el método del hidrómetro densímetro (Bouyoucos, 1962). Para ello, la muestra se mezcló con polifosfato de sodio y agua destilada, agitó, homogeneizó y procesó como está descrito en Primo & Carrasco (1973).…”
Section: Materiales Y Métodosunclassified